Development of the Information System Structure for Continuous Improvement of QMS in an Educational Institution; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Menshikova E. V. Ekaterina Valentinovna (2016, 2016)
Title screen